What would be the psychiatric diagnosis of D. Maria I, the “mad queen”? - Elie Cheniaux; Antonio Egidio Nardi; Marleide da Mota Gomes (Jornal Brasileiro de Psiquiatria, 2021)
ABSTRACT Objective D. Maria I, queen of Portugal, was the mother of João VI and grandmother of Pedro IV of Portugal and I of Brazil. She became the first monarch of Brazil, where she became known as “Maria, the madwoman”. We aimed to try to identify the mental disorder she suffered from. Methods We conducted a review of biographies about D. Maria I and scientific articles that discussed her case. Results The sparse information about her mental illness strongly indicates that she had several depressive and manic episodes, which were accompanied by psychotic symptoms. Conclusion Her probable psychiatric diagnosis is that of bipolar disorder.